Microcontroller-based Prototype Model of a Solar Wireless Electric Vehicle-to-Vehicle Charging System with Real-Time Battery Voltage Monitoring - Priyadarshini, M. S.; Mahmoud, M. Metwally; Sur, Ujjal; Ardjoun, Sid Ahmed El Mehdi; Hysa, Azem; Bessous, Noureddine; Metwally, Khaled A.; Anwer, Noha (Universitas Ahmad Dahlan, 2025)
The increasing adoption of electric vehicles (EVs) necessitates sustainable and efficient charging solutions, particularly in remote areas and emergency situations where conventional grid-based charging stations are inaccessible. This research presents an Arduino-based prototype model of the Solar Wireless Electric Vehicle-to-Vehicle Charging System (SWEV2VCS), integrating a TP4056 charging module, a microcontroller, and wireless power transfer (WPT) coils to facilitate efficient, autonomous charging. The system harvests solar energy through high-efficiency photovoltaic (PV) panels, which is then regulated and stored in lithium-ion batteries. The TP4056 module ensures safe and controlled charging by providing overcharge, over-discharge, and current regulation for battery protection. An Arduino-based microcontroller unit (MCU) is implemented to monitor and optimize power management, ensuring effective energy distribution and preventing inefficiencies. Wireless power transfer is achieved using electromagnetic resonance coupling, which enhances transmission efficiency over short distances. The system employs primary and secondary copper coils designed for resonant inductive coupling, enabling energy transfer between EVs without requiring a physical connection. The design and implementation include real-time battery voltage monitoring using an Arduino Nano and an I2C-based LCD display. The microcontroller measures battery voltage from an analogy pin, processes the data, and displays it on the LCD screen. The voltage sensing mechanism employs analogy-to-digital conversion (ADC) to ensure accurate readings. The LCD module provides real-time updates, enhancing user interaction and monitoring efficiency. The experimental setup verifies system functionality by continuously displaying voltage readings, facilitating better power management during wireless charging. This prototype serves as a fundamental step toward the development of automated, real-time monitoring systems in wireless EV charging applications.